Light transmission properties in inhomogeneously‐disordered random media. Issue 5 (10th March 2017) - Xu, Yuchen; Zhang, Hao; Lin, Yujun; Zhu, Heyuan
Abstract : The present work investigates the light transmission properties in disordered samples with inhomogeneous disorder geometries. The equivalence in the case of longitudinal inhomogeneous disorder is verified while such equivalence cannot be found in the case of transversely inhomogeneous disorder. Moreover, in the case of transverse disorder geometry, a most transmitted incident channel emerges as shown in the figure. Abstract : Spatially inhomogeneous disorder exists widely in optical systems. We present a numerical study on the light transport properties and analysis of transmission channels in random media with inhomogeneous disorder. For the case of longitudinal inhomogeneity of disorder we find that the statistics of the transmission channels is independent of the inhomogeneity and the system can be equivalent to a counterpart with homogeneous disorder strength, both of which have the same statistical distribution of the transmission channels. However, for the case of transverse inhomogeneity of disorder, such equivalence does not exist. The distribution of the total transmission is broadened and one most transmitted incident channel emerges.